Distal partial gastrectomy for gastric tube cancer with intraoperative blood flow evaluation using indocyanine green fluorescence. Issue 12 (24th December 2021) - Sakai, Ayano; Okumura, Tomoyuki; Miwa, Takeshi; Watanabe, Toru; Numata, Yoshihisa; Araki, Misato; Ito, Ayaka; Kanaya, Emi; Sakurai, Taro; Fukazawa, Mina; Hoshino, Yui; Tohmatsu, Yuuko; et al.
Abstract: With recent advances in the treatment of esophageal cancer and long-term survival after esophagectomy, the number of gastric tube cancer (GTC) has been increasing. Total gastric tube resection with lymph node dissection is considered to be a radical treatment, but it causes high post-operative morbidity and mortality. We report an elderly patient with co-morbidities who developed pyloric obstruction due to GTC after esophagectomy with retrosternal reconstruction. The patient was treated using distal partial gastric tube resection (PGTR) and Roux-en-Y reconstruction with preservation of the right gastroepiploic artery and right gastric artery. Intraoperative blood flow visualization using indocyanine green (ICG) fluorescence demonstrated an irregular demarcation line at the distal side of the preserved gastric tube, indicating a safe surgical margin to completely remove the ischemic area. PGTR with intraoperative ICG evaluation of blood supply in the preserved gastric tube is a safe and less-invasive surgical option in patients with poor physiological condition.